Endometrioid adenocarcinoma in pregnancy: case report - E V Musina; T G Tral; M A Tarasova (IP Berlin A.V., 2016)
Malignant tumors are encountered in pregnancy in cases of 0.07-0.1% of all pregnancies. Endometriod adenokratsinoma is an extremely rare disease in pregnancy. However there is the urgency of oncological vigilance against endometrial adenocarcinoma in women of reproductive age, including the background of pregnancy.